Identifikasi Lokasi Potensial dan Prioritas Pengembangan Agroindustri Aren di Kabupaten Tasikmalaya, Jawa Barat - Thoriq, Ahmad (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Tanah Laut, 2022)
Sugar palm is a plantation crop that has benefits economic, ecological, social and cultural, but the exploitation of palm sugar is generally still taking the results of plants that grow naturally. Identification of the distribution of sugar palm plants needs to be done to obtain priority locations for the development of sugar palm agro-industry. The potential location shows that the sugar palm has a comparative and competitive advantage compared to other plantation commodities. Comparative and competitive advantages can be determined using the Location Quotient (LQ) and Differential Shift (DS) methods, while the priority for developing sugar palm agro-industry products is determined by the exponential comparison method with criteria 1) market potential, 2) environmental sustainability and waste minimization, 3) availability of raw materials and supporting material, 4) local government support, 5) human resource capability, 6) availability of applicable technology, 7) competitiveness of similar products and substitute products, and 8) efficiency of production costs. The results showed that the potential location of sugar palm plants were found in five districts in Tasikmalaya Regency, among others Ciawi districts, Cigalontang districts, Jamanis districts, Jatiwaras districts, and Sukahening Districts. The priority of developing agroindustry products based on the analysis of the corresponding exponential comparison method is palm sugar (10.21), palm fruit (10.20), palm fiber (10.19), ant sugar (10.17) and palm starch flour (10.06).